A Comparative Study on Efficacy of Methotrexate and Sulphasalazine in Spondyloarthropathies - Afsar, NS; Khan, MMN; Chowdhury, MMH; Haq, SA; Rahman, M Khalilur; Khan, MMR (TAJ: Journal of Teachers Association, 2011)
Background: Spondyloarthropathies include a wide spectrum of disease. The study was conducted with the aim of observing the efficacy of SSZ and MTX in different subclasses of spondyloarthropathies and to compare the treatment response of the two drugs. Methods: This study was conducted in the Department of Medicine and Rheurnatology clinic of Bangabandhu Sheikh Mujib Medical University (BSMMU) between January 1999 and July 2001.A total number of one hundred twenty five patients was included in the study. Patients with active disease more than three months, regularly taking NSAIDs and not on DMARD in the last three months were included in the study. Monthly follow up of the patients was done for 6 months. Result: One hundred twenty five patients were included in this study. Male female ratio was 11.5:1. Mean age of patients was 24.17±7.15 years. The mean disease duration was 47.8±32.8 months. The present study categorized the patients into responder and non responder. Among the 78 patients in AS subclass, after completion of 6 month trial 55.6% patients in SSZ group and 39.4% patients in MTX group were categorized responder. The difference of response between drug groups was not significant (p=0.158). In the JCA subclass 81.82% in SSZ and 50% in MTX group were responder. The numbers of patient in Reiter's/Reactive Arthritis in our study were too small to make a definite comment. Conclusion: It can be concluded from this study that both the SSZ and MTX are effective DMARDs for spondyloarthropathies. Statistical analysis did not prove superiority of one drug over another, though the response rates were numerically higher in SSZ group. TAJ 2011; 24(1): 43-47